(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Field trials were conducted at Teaching and Research Farm of Federal University, Dutsina, Katsina State and Institute for Agricultural Research Station, IAR, Minjibir Kano State during 2019 wet season. The experiment was carried out to evaluate the growth, Yield and Yield Components of Groundnut varieties as influenced by phosphorus fertilization in Sudan Savannah of Nigeria. The treatments consisted of three Groundnut varieties (SAMNUT 23 and SAMNUT 24 and SAMNUT 25) and four phosphorus fertilizer rates (0kg P/ha, 20kg P/ha, 30kg P/ha and 40kg P/ha), laid out in Randomized Complete Block Design (RCBD) with three replications. The results indicated that SAMNUT 23 had performed significantly (Pâ‰¤0.05) better than SAMNUT 24 and SAMNUT 25 in terms of plant height, number of leaves per plant, number of pods per plant, pod weight kg/plot, 100 seed weight and grain yield kg/ha at both locations while 40kg P/ha significantly (Pâ‰¤0.05) outperformed 30kg P/ha, 20kg P/ha and 0kg P/ha in terms of plant height, number of leaves, number of pods per plant, pod weight kg/plot, 100 seed weight and grain yield kg/ha at both locations . the study identified SAMNUT 23 and 40 kg P/ha to be the best option for increased groundnut production in the study area